Ser Todo é Ser Parte - Mariana Oliveira, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Ser Todo é Ser Parte [To be Whole is to be Part] - Illustration